Occupational Safety and Health of Riders Working for Digital Food Delivery Platforms in the City of Milan, Italy - Boniardi, Luca; Campo, Laura; Prudenzi, Sofia; Fasano, Luciano; Natale, Paolo; Consonni, Dario; Carugno, Michele; Pesatori, Angela Cecilia; Fustinoni, Silvia (La Medicina del Lavoro, 2024)
Background: The rapid growth of the digital economy has transformed various labor markets, including the food sector. The transient nature and the peculiar work environments of food delivery workers raise concerns about occupational safety and health (OSH). This study aims to better understand these issues by conducting a comprehensive exploratory survey on OSH among food delivery riders in Milan, Italy. Methods: The study employed structured interviews based on a validated questionnaire developed through a literature review, expert interviews, and input from riders and health and safety professionals. The survey was performed from July to November 2022 by interviewing riders at their main gathering points. Results: We interviewed 240 riders, 97% males, 81% less than 35 years old, and 83% with extra-European origin. Delivery was performed mainly by traditional bicycles (40%) and e-bikes (46%), with 44% working seven days per week and 23% working more than 8 hours daily. Road accidents were reported by 39% of riders, influenced by type of vehicle, fatigue, and number of daily deliveries. Physical and verbal assaults (12% and 28%, respectively) were reported, as well as health-related issues, particularly musculoskeletal disorders. Conclusions: The findings underscore food delivery riders’ complex challenges, emphasizing the need for targeted interventions. The study calls for collaborative efforts between policymakers, employers, OSH professionals, and stakeholders to enhance OSH standards and promote decent working conditions, aligning with the 2030 Agenda for Sustainable Development.